How do the epidemiology of paediatric methicillin‐resistantStaphylococcus aureusand methicillin‐susceptibleStaphylococcus aureusbacteraemia differ?. Issue 6 (June 2017) - Abernethy, Julia; Sharland, Mike; Johnson, Alan P.; Hope, Russell
Abstract : Purpose. : To examine whether the epidemiology of bacteraemia caused by methicillin‐susceptible Staphylococcus aureus (MSSA) and methicillin‐resistant S. aureus (MRSA) differed in children aged <1 year and in comparison to older age groups. Methodology. : English mandatory MRSA and MSSA surveillance data from 2006 and 2011, respectively, were collected. Epidemiological information was descriptively analysed in relation to methicillin susceptibility and patient age. Ninety‐five percent confidence intervals (CIs) are reported. Results/Key findings. : The average incidence rate of MSSA and MRSA bacteraemia in <1‐year‐olds was 60.2 and 4.8 episodes per 100000 population per year, respectively. Of the cases of MSSA bacteraemia in children aged <1 year, 47.5% (95% CI: 45.1‐50.0; n =760/1599) were in neonates. With increasing age up to one year, more MSSA bacteraemias were detected ≥7 days after admission, ranging from 0% (95% CI: 0‐2.5%) in 0‐2‐day‐olds to 68.4% (95% CI: 64.0‐72.5%; 333/487) in 8‐28‐day‐olds and 50.5% (95% CI: 47.1‐54.0%; 423/837) in 29 day‐1‐year‐olds, a higher proportion than in older children but similar to MRSA bacteraemia. Amongst <1‐year‐olds with MSSA bacteraemia, the underlying source was most commonly recorded as intravascular devices [34.4% (95%, CI: 30.5‐38.6%); n =190/552] whilst in older age groups this declined. A similar trend was observed for MRSA bacteraemia. Conclusions. : Our analysis indicates that S. aureus bacteraemia in <1‐year‐olds is primarily healthcare‐associated, unlike MSSA bacteraemia in older age groups. Paediatric‐specific interventions targeted at the healthcare setting, such as neonatal unit‐specific care bundles and paediatric device‐specific strategies, are required.